Opozice na Slovensku v letech 1968-1989 - Halla, Josef, 1972-; Goněc, Vladimír, 1950-; Masarykova univerzita. Historický ústav (2018)
Anotace Disertace popisuje situaci opozice na Slovensku mezi roky 1968 a 1989. Úvodní část se věnuje archivním pramenům v České republice a na Slovensku, problémům při jejich výzkumu a zmiňuje nejdůležitější literaturu. Druhá část se zaobírá politickou situací v Československu v době před pražským jarem, v roce 1968 a v prvních letech normalizace. Třetí část analyzuje nejrůznější typy opozice (disentu) proti komunistickému režimu na Slovensku v období normalizace mezi lety 1968 a 1989 - náboženskou opozici, občanskou opozici, snahy maďarské menšiny, ekologické hnutí, neoficiální uměleckou scénu, jejich činnost a vliv na společnost. Významný vliv pro činnost opozice měl samizdat. Práce vyjmenovává jednotlivé formy a metody perzekuce a uvádí příklady významných osobností slovenské opozice. Následuje závěr, seznam zkratek, pramenů a literatury a obrazové přílohy (archivní dokumenty, fotografie)
Annotation The disertation describes the situation of opposition in Slovakia between the years 1968 and 1989. The first part focuses on the archival sources in the Czech Republic and Slovakia, the problems of their research and the most important literature of Czech and Slovak historians. The second part deals with the political situation in Czechoslovakia before the Prague Spring, in 1968 and the first years of normalization. The third part analyses different types of opposition (dissent) against the communist regime in Slovakia during the period of normalization between the years 1968 and 1989 - religious opposition, civil opposition, efforts of the Hungarian minority, environmental movement, an unofficial artistic scene, their activities and influence on the Slovak society. Importance influence at the activity of opposition had a samizdat. This dissertation lists individual forms and methods of persecution and gives examples of important personalities of the Slovak opposition. The f
Vedoucí práce: Vladimír Goněc
Dizertace (Ph.D.)--Masarykova univerzita, Filozofická fakulta, 2019
Keywords: 1968-1989; 20. století; disent -- Slovensko -- 20. století; normalizace (1969-1989 : Československo); samizdat -- Slovensko -- 20. století; dissent -- Slovakia -- 20th century; "normalization" (1969-1989 : Czechoslovakia); samizdat -- Slovakia -- 20th century; Slovensko -- dějiny -- 20. století; Slovakia -- history -- 20th century; disertace; dissertations